PENDAMPINGAN MASYARAKAT KOTA SURABAYA DENGAN PENDEKATAN DOOR-TO-DOOR UNTUK KEPATUHAN WAJIB PAJAK BUMI DAN BANGUNAN - Aziz, Rizqi Nurul Afifa; Nisa, Fauzatul Laily; Oktafia, Renny (Jurnal Abdimas Bina Bangsa, 2025)
Land and Building Tax (PBB) has an important role in supporting Surabaya City's Local Revenue (PAD). However, the low level of taxpayer compliance is a major challenge in local tax management. This study aims to evaluate the effectiveness of the door-to-door approach implemented by the Surabaya City Regional Revenue Agency (Bapenda) in increasing the awareness and compliance of PBB taxpayers. Through direct socialization, tax officers provide education and resolve administrative issues, such as arrears and data discrepancies with field results. The results showed that this method succeeded in increasing PBB revenue by 8.74% and helped boost PAD. The door-to-door approach proved effective in raising taxpayers' awareness and improving their compliance levels. This success contributed positively to the achievement of Surabaya City's PAD target. This approach can be adapted to improve public understanding of tax obligations and is expected to become a broader model in local tax management